Peran Manajemen Pemberdayaan Ekonomi Masyarakat dalam Mendukung Pencapaian Tujuan Pembangunan Berkelanjutan (SDGs): Studi Empiris di Kabupaten Hulu Sungai Utara, Indonesia - Erfan Maulana; Muhammad Rais Arifin; Lalu Muhammad Abdul Azis (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Community economic empowerment is widely recognized as a strategic instrument for accelerating the achievement of the Sustainable Development Goals (SDGs), particularly in developing regions. This empirical study examines the role of community economic empowerment management in supporting SDGs achievement in Hulu Sungai Utara Regency, South Kalimantan, Indonesia. Employing a mixed-methods approach, the study integrates quantitative survey data from 120 respondents with qualitative in-depth interviews involving 15 key informants, supported by secondary data analysis and a review of reputable literature. The findings reveal that effective empowerment management characterized by structured planning, access to capital, training effectiveness, institutional coordination, and outcome-based monitoring has a significant positive impact on income improvement, business sustainability, and employment stability. Although Hulu Sungai Utara Regency demonstrates a relatively low poverty rate, managerial and institutional challenges limit the optimal contribution of empowerment programs to SDGs targets. This study contributes empirical evidence from a local Indonesian context and proposes a management-oriented framework for aligning community empowerment initiatives with sustainable development agendas